2012
DOI: 10.1097/aln.0b013e318242349a
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning Applied during Isoflurane Inhalation Provides No Benefit to the Myocardium of Patients Undergoing On-pump Coronary Artery Bypass Graft Surgery

Abstract: RIPC applied during isoflurane inhalation provides no benefit to the myocardium of patients undergoing on-pump coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 45 publications
0
90
0
3
Order By: Relevance
“…Only 2 studies, one of them with only 4 patients per group, reported an increased infarct size with remote ischemic preconditioning. 127,128 Other studies were either neutral 36,38,[129][130][131][132][133][134][135][136][137][138] or had significantly reduced infarct size, as reflected by reduced biomarker release 37,139-149 ( Figure 3). Only one study each found improved clinical outcome at short-term 149 or more long-term follow-up.…”
Section: Remote Ischemic Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2 studies, one of them with only 4 patients per group, reported an increased infarct size with remote ischemic preconditioning. 127,128 Other studies were either neutral 36,38,[129][130][131][132][133][134][135][136][137][138] or had significantly reduced infarct size, as reflected by reduced biomarker release 37,139-149 ( Figure 3). Only one study each found improved clinical outcome at short-term 149 or more long-term follow-up.…”
Section: Remote Ischemic Conditioningmentioning
confidence: 99%
“…Propofol is known to abrogate protection by remote ischemic conditioning, which is seen with volatile anesthesia, 153,[162][163][164] and volatile anesthesia is the recommended anesthesia for patients at cardiac risk. 233,234 As seen from Figure 3, the only study with a significant increase of infarct size 128 and all neutral studies where information on the anesthetic regime is available 36,38,[130][131][132][133][135][136][137][138]150,155 had used propofol anesthesia, which, therefore, appears as the major denominator of all neutral/negative studies on remote ischemic conditioning in cardiovascular surgery.…”
Section: Current State Of Translation For Remote Ischemic Conditioningmentioning
confidence: 99%
“…Omitting the 4 studies using another protocol than the mainly used 3×5-min remote conditioning protocol from analysis, barely affected the heterogeneity (I 2 =68%, P=0.0009), and changed the pooled SMD in favor of RIC (-0.46, 95% CI: -0.76 to -0.16) in the Characteristic a Kottenberg et al 24 Lucchinetti et al 25 Hong et al 26 Target Figure 4B). 6,7,17,20,21, 23 Sensitivity analysis showed that the omission of each study one at a time did not appreciably change the pooled SMD, and the estimates in each case were within the CI of the pooled estimate ( Figure 5).…”
Section: Cabgmentioning
confidence: 99%
“…Согласно их данным [23] прекондиционирование не ока-зывает нейропротекторного эффекта. У пациентов с КШ канад-ские анестезиологи оценивали повреждение ГМ по уровню в плазме крови белка S-100 [24]. ДП воспроизводили с помощью 4 циклов ишемии (5 мин) и реперфузии (5 мин) нижней конечно-сти после наркоза изофлураном перед КШ.…”
Section: контактная информацияunclassified
“…Оказалось, что ДИП не влияет на уровень S-100 в крови. Авторы заключили, что ДИП не оказывает нейропротекторного эффекта у больных с КШ [24]. В исследование, выполненное в России, были включены 88 па-циентов, которым выполнялось КШ в условиях ИК [25].…”
Section: контактная информацияunclassified